Elemental composition of fruits and vegetables using INAA, AAS, and ICP-MS - Shafaei, Mohammad Ali (2012)
Industrial growth has provided peerless progress in living standards and comforts for mankind, but it has been the cause of menace of environmental pollution. The issues like chemical toxicology, acid rain, greenhouse effect, ozone depletion, industrial effluents, and marine pollution are universal in nature. Man is being unceasingly divulged to a large number of inorganic elements in a great variety of chemical forms and when they enter the human body they can cause toxicity effects resulting in deterioration of man general health. Knowledge of base line data of elemental compositions in fruits and vegetables is important to manage dietary adequacy of the population. In Malaysia, no systematic study on the dietary adequacy of essential heavy elements through fruits and vegetables has been published. The purpose of the present study is to determine the concentration of essential elements in fruits and vegetables and to extrapolate the data for the dietary adequacy and regional dietary standards. Instrumental Neutron Activation Analysis (INAA), Atomic Absorption Spectrometry (AAS) and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) were employed in this study to determine the major elements (K, Mg, Ca) and heavy metals (Fe, Zn, Cu, Mn, Al, Co, Se, Ni, As, Hg, Pb, Cd, Cs, Th, Cr, La) of 14 types of fruits and 11types of vegetables planted in Malaysian. Neutron irradiation and counting were performed using 500 kW of 1.1 MW TRIGA Mark at the Malaysian Nuclear Agency’s research reactor. Sample powder was irradiated with thermal neutrons at flux average of =2.03×1012 n.cm-2.s-1 and the analysis was carried out using a hyper-pure germanium (HPGe) detector, multichannel analyzer module and Gamma Vision software. Biological standard materials (NIST-Tomato Leaves 1537a) and soil standard materials (IAEA-SOIL-7) were used as reference materials in the INNA technique. In ICP-MS, the elements of solution sample were identified by their mass-to-charge ratio (m/e) and the intensity of a specific peak in the mass spectrum is proportional to the amount of that element in the sample. In AAS, the solution sample was atomized before allowing light to pass and produced a line absorption spectrum, characteristics of the particular elements in the fruits and vegetables. No biological standard materials are needed in ICP-MS and AAS techniques. Samples were collected from a number of fresh markets at the centre of Kuala Lumpur, the capital of Malaysia and transported to the laboratory within one day to prepare the final samples for INAA, ICP-MS and AAS techniques. The results of INAA, ICP-MS and AAS analyses, we found that there is a variation in the amount of each element for Malaysian fruits and vegetables. For the major elements (K, Mg, Ca), K concentrations in fruits were from 10,615±500 ppm (Jasopine pineapple) to 33,353±600 ppm (melon) and from 9,749±1000 ppm (eggplant) to 51,196±900 ppm (red spinach) in vegetables. Mg concentrations in fruits were from 680±30 ppm (Morise pineapple) to 5,543±400 ppm (red banana) and from 690±140 ppm (carrot) to 3,852±500 ppm (cucumber) in vegetables.Ca concentrations were from1,064±127 ppm (baby banana) to 6,888±800 ppm (durian) in fruits and from 1100±130 ppm (chili) to 8,000±900 ppm (green bean) in vegetables. For the heavy metal elements in fruits Mn concentration ranged from 12.0±0.5 ppm (Morise pineapple) to 69±1 ppm (Max banana), Fe concentration from 23.4±2.8 (papaya) to 126±15 ppm (watermelon), and Zn concentration from 19±2 ppm (max banana) to 168±20 ppm (pisang banana). While for the heavy metal elements in vegetables, Mn concentration ranged from 32.0±0.9 ppm (carrot) to 316±16 ppm (spinach), Fe concentration from 58±3 (pumpkin) to 470±56 ppm (spinach), and Zn concentration from 26±3ppm (pumpkin) to 312±37 ppm (spinach). The percentage intake of all elements was calculated for the Recommended Dietary Allowance (RDA) values for Malaysian fruits and vegetables per 100 g of eatable section. The highest percentage intakes of elements are for K, Mg, Ca, Mn, Zn, Cu,Ni, Al, and Fe, which can be achieved from eating Malaysian fruits and vegetables.Co in spinach and star fruit were found to be the highest percentage intake of vegetables and fruits. Based on this result, spinach and star fruit can be a good source of Co, respectively each vegetable and fruit with 35% and 5% supply of this element to the recommended value of Co in the form of vitamin B12. An interesting point is that; the mean range of Pb, Hg, and Cd is lower than the tolerable upper intake level (UL), and some of the other elements such as Cr, Cs, and Se, showed near the range of UL for Malaysian fruits and vegetables, for example, Cr in durian, guava, papaya, cabbage, chili, chili padi, spinach, and red spinach, and Cs and Se, in durian and carrot respectively. The statistical dependence between concentrations of element presents in fruits and vegetables and between types of fruits and vegetables were determined using the cluster analysis. According to the cluster analysis, the results revealed similarity in two or more than two of different fruits or vegetables, dose not mean the same affection on nutrition health.